RODES software for dose assessment of rats and mice contaminated with radionuclides. (31st January 2017) - Locatelli, Maxime; Miloudi, Hanane; Autret, Gwennhael; Balvay, Daniel; Desbrée, Aurélie; Blanchardon, Eric; Bertho, Jean-Marc
Abstract: In order to support animal experiments of chronic radionuclides intake with realistic dosimetry, voxel-based three-dimensional computer models of mice and rats of both sexes and three ages were built from magnetic resonance imaging. Radiation transport of mono-energetic photons of 11 energies and electrons of 7 energies was simulated with MCNPX 2.6c to assess specific absorbed fractions (SAFs) of energy emitted from 13 source regions and absorbed in 28 target regions. RODES software was developed to combine SAF with radiation emission spectra and user-supplied biokinetic data to calculate organ absorbed doses per nuclear transformation of radionuclides in source regions ( S -factors) and for specific animal experiments with radionuclides. This article presents the design of RODES software including the simulation of the particles in the created rodent voxel phantoms. SAF and S -factor values were compared favourably with published results from similar studies. The results are discussed for rodents of different ages and sexes.